Renal cell carcinoma of horseshoe kidney - Tufegdžić Milomir; Vasić Vladimir; Hadži-Đokić Jovan (Srpski Arhiv za Celokupno Lekarstvo, 2020)
Introduction. Horseshoe kidney is the most common developmental disorder of the urinary system, which involves an anomaly of kidney fusion, and occurs in 3% of the population. Kidneys are most often connected at the lower poles by fibrous or parenchymal isthmus. Renal cell carcinoma (RCC) is the most common tumor of the horseshoe kidney. Treatment involves surgical treatment that includes heminephrectomy or partial nephrectomy with different approaches. We report a case of RCC of a horseshoe kidney, located on the lower pole and the isthmus. Case outline. A 68-year-old patient reported to the urologist due to intermittent painless macroscopic hematuria. Computed tomography urogram revealed the presence of a tumor on the right kidney, measuring 85 × 90 × 60 mm, with radiological characteristics of RCC, which covered the entire lower pole of the kidney towards the isthmus. Angiography finding indicated a thickened isthmus with pronounced malformation of vascular structures. The right heminephrectomy was performed with resection of the isthmus from 15 mm to the healthy tissue. The isthmus was sutured in two layers with a catgut suture. Subsequently, hilar, paracaval, and interaortocaval lymphadenectomies were performed. The pathohistological finding indicated a tumor of renal cell origin, while the resection line was free of the tumor tissue, as were the lymph nodes. Conclusion. RCC is the most common neoplasm of the horseshoe kidney. Treatment is surgical and involves open or laparoscopic heminephrectomy or partial nephrectomy with a transperitoneal or extraperitoneal approach.